Diversity and Context in Health Ethics: The Case for Rural Health - Mashmoushi, Yasmina; Mzouri, Mitan (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2018)
This review maintains that the book, Rethinking Rural Health Ethics, is essential reading for rural health providers, rural health policy makers, and rural health ethicists because it uncovers the fundamental inadequacies of the traditional, urban-centric health ethics framework with respect to the rural health setting and formulates the basis for a more viable and distinctive rural health ethics. This review further maintains that this book possesses far-reaching, robust implications on the importance of incorporating diversity and context into ethical deliberations within the broader field of health ethics and in all levels of ethical analysis (i.e., micro, meso, and macro), thus serving as a resonating and sage influence for health ethicists in all fields.